2010
DOI: 10.1088/0264-9381/27/4/045006
|View full text |Cite
|
Sign up to set email alerts
|

On the calculation and interpretation of MSA coordinates

Abstract: The static solutions of the axially symmetric vacuum Einstein equations with a finite number of Relativistic Multipole Moments (RMM) are described by means of a function that can be written in the same analytic form as the Newtonian gravitational multipole potential. A family of so-called MSA (Multipole-Symmetry Adapted) coordinates are introduced to perform the transformation of the Weyl solutions; a procedure for their calculation at any multipole order is given, and the results for a low order are shown.In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 22 publications
4
46
0
Order By: Relevance
“…We shall back to the explicit expression forr 1 later, but previously let us redefine the problem to solve enunciated at Statement 1. In accordance with the discussion in [1] we have showed that conditions (i)-(ii) lead to the same equations that the pair of conditions (i)-(iii), and therefore the problem we want to solve is now formulated as follows: Statement 2 Letr =r(x, y),ŷ =ŷ(x, y) be a pair of surfaces with the relationship given by the expression (15). Then, the radial coordinate of the MSA system of coordinates {r,ŷ} with which the MQ-solution is described by the metric function g M Q 00 = −1 + 2M r + 2QP 2 (ŷ) r 3 , is given by the solution of the differential equation (16) with the boundary conditionr(x, y = ±1) =r 1 and asymptotic conditionsr(R → ∞) = R + α,ŷ(R → ∞) = ω.…”
Section: Resolution Strategiessupporting
confidence: 90%
See 4 more Smart Citations
“…We shall back to the explicit expression forr 1 later, but previously let us redefine the problem to solve enunciated at Statement 1. In accordance with the discussion in [1] we have showed that conditions (i)-(ii) lead to the same equations that the pair of conditions (i)-(iii), and therefore the problem we want to solve is now formulated as follows: Statement 2 Letr =r(x, y),ŷ =ŷ(x, y) be a pair of surfaces with the relationship given by the expression (15). Then, the radial coordinate of the MSA system of coordinates {r,ŷ} with which the MQ-solution is described by the metric function g M Q 00 = −1 + 2M r + 2QP 2 (ŷ) r 3 , is given by the solution of the differential equation (16) with the boundary conditionr(x, y = ±1) =r 1 and asymptotic conditionsr(R → ∞) = R + α,ŷ(R → ∞) = ω.…”
Section: Resolution Strategiessupporting
confidence: 90%
“…In [1], a coordinate transformation with a good asymptotic Cartesian behaviour was performed as followŝ…”
Section: Resolution Strategiesmentioning
confidence: 99%
See 3 more Smart Citations